Corporate Social Responsibility Sebagai Mediasi Pengaruh Environmental Performance Dan Implementasi Green accounting Terhadap Sustainable Development - Zanra, Sri; Zubir (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to examine the effect of Environmental Performance and Green accounting implementation on Sustainable development with Corporate social responsibility as a moderating variable. The population of this study is public manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the basic industry and chemical sub-sectors in the period 2021-2023.The sample of this study was selected using the purposive sampling method. Data were collected through the official website of the Indonesia Stock Exchange and other related sources, and by studying literature relevant to the research topic, both in print and electronic media. Data analysis was carried out using the Partial Least Square (PLS) technique. The results of the study revealed that the implementation of Green accounting and Environmental Performance have an positif  effect on Sustainable Development. In addition, Corporate social responsibility has been proven to moderate the relationship between the implementation of Green accounting and Environmental Performance with Sustainable Development. The research results can provide guidance for companies in formulating effective CSR strategies, which not only improve reputation but also support environmental performance and Green accounting.